Case Report: Hyperbilirubinemia in Gilbert Syndrome Attenuates Covid-19-Induced Metabolic Disturbances - Al-kuraishy, Hayder M.; Al-Gareeb, Ali I.; Abdullah, Saleh M.; Cruz-Martins, Natália; Batiha, Gaber El-Saber (Frontiers in Cardiovascular Medicine, 2021)
Gilbert syndrome (GS) is a liver disorder characterized by non-hemolytic unconjugated hyperbilirubinemia. On the other hand, Coronavirus disease 2019 (COVID-19) is a recent viral infectious disease presented as clusters of pneumonia, triggered by the severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2). Little is known on the association between SARS-CoV-2 and GS, despite different studies have recently stated a link between hyperbilirubinemia and SARS-CoV-2 severity. In this case-report study we described a 47-year-old man, a known case of GS since the age of 4, presented to the emergency department with fever (39.8 ºC), dry cough, dyspnea, headache, myalgia, sweating and jaundice diagnosed with COVID-19-induced pneumonia. Interestingly, GS patient exhibited a rapid clinical recovery and short hospital stay compared to other SARS-CoV-2 positive patient, seeming that hyperbilirubinemia may exert a protective effect of against COVID-19 induced-cardiometabolic disturbances. Data obtained here underlines that the higher resistance against COVID-19 evidenced by the GS patient seems to be due to the antioxidant, anti-inflammatory, and antiviral effects of unconjugated bilirubin.